The Importance of Being Human: A Case Study of Library, Archives, and Museum Collaboration. Issue 2 (June 2014) - Fox, Heather
Libraries, Archives, and Museums (LAM) convergence has been a topic of discussion for nearly a decade, with a particular focus on harnessing technological know-how to create efficiencies around managing and providing access to collections cared for by these similar yet distinct professions. This case study examines the interaction amongst the University of Louisville (U of L) Art Library, U of L Archives, and the Speed Art Museum (Speed) as the three separate entities worked together to complete an IMLS-funded grant project focused on streamlining the Speed's library. Although the initial work centered on surveying and weeding the Speed's collection and creating electronic catalog records of the materials, shifts in the grant budget supported the hiring of a Project Archivist to transfer the Speed's institutional archives to the University of Louisville. This formal partnership developed from a history of informal collaboration, impelled by exigencies of impending construction to create a new museum space. The project improved access to Speed Library's collection, enhanced the U of L Art Library's collection and facilitated preservation of and provided access to the institutional records of the Speed Art Museum. In addition, conversations about LAM convergence tend to emphasize technology. This case study draws on the Collaboration Continuum introduced by Zorich, et al in a 2008 report on the topic and examines the power of interpersonal relationships, which ultimately proved to be the important drivers of this collaboration.